Flexing di Media Sosial: Antara Gaya Hidup dan Tekanan Sosial pada Mahasiswa Sosiologi Universitas Sriwijaya - Febiani, Selvia; Dewi Pergiwati Wijaya; Sharen Sakita (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The development of digital technology has significantly changed the way students interact and present themselves in social life, especially through social media such as Instagram, TikTok, and Twitter. One of the emerging social phenomena is flexing, which refers to the behavior of showing off lifestyle, achievements, or ownership to gain attention and social recognition. This study aims to analyze how Sociology students of Sriwijaya University interpret flexing on social media and whether flexing is more dominant as a lifestyle or as a form of social pressure. This research uses a qualitative method with a literature review approach by examining various scientific articles, journals, and previous studies related to flexing, self-presentation, symbolic consumption, social validation, and Fear of Missing Out (FoMO). The results show that flexing is not only a form of self-presentation and symbolic consumption, but also a response to social pressure in the digital environment.